RESTRUKTURISASI STATUS RUMAH SAKIT UMUM DAERAH PADANGAN BOJONEGORO DARI SATUAN KERJA PERANGKAT DAERAH MENJADI BADAN LAYANAN UMUM DAERAH - Apriliyanto, Dimas Rahardiyan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This Research aims to know the restructuring process Padangan General Hospital from Regional Work Unit to Public Service Agency, various constraints faced by Padangan General Hospital as well as the solution to overcome those obstacles, and various advantages or disadvantages received by the patients or the hospital when it becomes Public Service Agency. The type of this research is case study research with quantitative descriptive approach. Data used in this research are both quantitative data and qualitative data. The data source was attained through interview and various documents directly from Padangan General Hospital. Data analysis in this research is done through measuring the feasibility of Padangan General Hospital to be Public Service Agency by using two indicators such as service indicators provided to the public and financial performance indicators of Padangan General Hospital based on Cost Recovery Rate Method. The researchers also analyzed the transformation process of Padangan General Hospital from Regional Work Unit to Public Service Agency by comparing the procedures based on Law No. 23 in 2005 about Financial Management of Public Service Agency to the existing reality. Based on the conducted data analysis, it concludes that Padangan General Hospital is feasible to be upgraded to Public Service Agency; further, the result of restructuring processes taken by Padangan General Hospital demonstrate some changes on organizational structure, employee recruitment and selection processes, asset management and procurement processes, as well as financial management. By becoming Public Service Agency, it is expected that Padangan General Hospital can improve its service performance provided to the population and able to be more self-dependent in financing its entire operation. Keywords: Restructuring, Public Service Agency, Padangan Hospital, Financial Performance, Service Performance, Constraints, Advantage